Building Futures: Advocating for Enhanced Mental Health Accessibility in Diverse Communities - Tian, Fengyuan (International Journal of Social Sciences and Public Administration, 2026)
Mental health accessibility is a critical public policy issue that affects individuals across diverse social contexts, including educational settings, prenatal care, disability services, and rural healthcare systems. This essay examines the systemic barriers that limit access to mental health services, such as socioeconomic inequality, racial discrimination, geographic constraints, and shortages of mental health professionals. Drawing on existing literature, the paper analyzes how these barriers manifest in four specific contexts: school-based mental health support for students with disabilities, prenatal mental health care for Black women, access to coordinated care for youth with Autism Spectrum Disorder, and pediatric mental health services in rural areas. Through a rhetorical and policy-oriented analysis, the essay highlights the limitations of current mental healthcare models and emphasizes the need for integrated, preventive, and inclusive approaches. By synthesizing evidence across these contexts, the paper argues that mental health accessibility requires systemic reform rather than isolated, setting-specific solutions, and calls for policymakers and institutions to prioritize equitable and universal access to mental health services.